Scoring Setting and Infrastructure di Kampus Politeknik Negeri Medan Berdasar UI GreenMetric - Taufiq, Muhammad; Carlo, Nasfryzal; Y Jumas, Dwifitra; Rita, Eva; Utama, Lusi (Structure, 2024)
Abstract - Green Campus is a concept that supports sustainable and environmentally sounddevelopment by involving the academic community in the campus environment. Campus Strategic Planof Medan State Polytechnic (Polmed) proclaims to be a green campus in 2025. One of Polmed's effortsto participate in sustainable development is by participating in the UI GreenMetric World UniversityRanking program. One of the assessment categories is Setting and Infrastructure. This researchfocuses on the Setting and Infrastructure indicator with the assessment criteria being the ratio of openspace to campus area, total campus area covered by forest vegetation, total campus area covered byplant vegetation, total campus area for water absorption, total open space area to campus population,percentage of campus budget for sustainable efforts, percentage of building operation andmaintenance activities in one year, campus facilities for the disabled, special needs, security and safetyfacilities, health infrastructure, conservation programs. The results showed that the score obtainedfrom the Polmed campus is currently 440 out of 1500 expected. To increase the score, a vertical gardenor rooftop garden can be implemented on the criteria of plant vegetation, making biopore infiltrationholes and replacing paving blocks with grass blocks on the criteria of water catchment areas, installingguiding blocks and making ramps for the criteria of facilities for the disabled, and blocking